Blending Better Beverage Options: A Nutrition Education and Experiential Workshop for Youths - Kathy K. Isoldi; Veronika Dolar (Hindawi Limited, 2015)
Objective. To reduce intake of sugar-sweetened beverages (SSBs) in youths as a means to reduce obesity risk. Methods. Youths 5-14 years old attending a summer program were given a two-hour workshop addressing the sugar content in SSBs, the health risks from drinking SSBs, and hands-on preparation as well as tastings of low-sugar beverage alternatives. Data on usual intake of SSBs was obtained at baseline, and pre- and postprogram surveys were conducted to gauge change in knowledge and/or attitudes regarding SSBs. Results. There were 128 participants (63% male) in the program. SSBs were commonly consumed with over 80% reporting regular consumption (mean daily intake 17.9 ounces). Significant increase in knowledge regarding the sugar content of commonly consumed SSBs was achieved; however change in attitudes was not significant. The large majority of youths reported enjoying the workshop and intention to reduce intake of SSBs following program participation. Conclusion. SSBs are commonly consumed by youths. Knowledge regarding the sugar content of SSBs is easier to impart to youths than influencing attitudes held about these beverages. Long-term interventions that reach out to parents and address the widespread availability of SSBs are needed to influence resistant attitudes and beverage choosing behaviors in youths.